Analysis of the Effectiveness of Using Accounting Information Systems in Financial Management through the Technology Acceptance Model Approach (Case Study at BKAD UPK, Pringgarata District, Central Lombok Regency) - Irawati, Sofya; Sodik, M; Puspitosarie, Endah; Hasan, Khojanah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This study analyzes the effectiveness of using an Accounting Information System in financial management at BKAD UPK Kecamatan Pringgarata Kabupaten Lombok Tengah using the Technology Acceptance Model (TAM) approach. A descriptive qualitative approach is applied to gain a deeper understanding of users' perceptions of the system. Data were collected through observation, questionnaires, interviews, and documentation. The analysis examines Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, and Behavioral Intention to Use in relation to the use of the Accounting Information System. The results indicate that although the system is easy to use, its usefulness remains low due to limitations in recording all transactions and presenting complete, accurate, and real-time integrated financial information. This affects users' overall attitude and intention toward the system, which tend to be negative, indicating that the current system is still ineffective for financial management. Therefore, this study emphasizes the need for a more modern, integrated, and real-time system to enhance financial management effectiveness at BKAD UPK Pringgarata District, Central Lombok Regency